(untitled) (Bangladesh Medical Journal, 2016)
The existence of a plethora of empirical evidence documenting the improvement of educational outcomes through the use of formative assessment is conventional wisdom within education. In reality, a limited body of scientifically based empirical evidence exists to support that formative assessment directly contributes to positive educational outcomes. The use of formative assessments, or other diagnostic efforts within classrooms, provides information that should help facilitate improved pedagogical practices and instructional outcomes. However, a review of the formative assessment literature revealed that there is no agreed upon lexicon with regard to formative assessment and suspect methodological approaches in the efforts to demonstrate positive effects that could be attributed to formative assessments. Thus, the purpose of this article was two-fold. First, the authors set out to clarify the terminology related to formative assessment and its usage. Finally, the article provides a critical analysis of the seminal literature on formative assessment. Bangladesh Med J. 2016 Jan; 45 (1): 47-53